2003
DOI: 10.1007/s00586-002-0518-3
|View full text |Cite
|
Sign up to set email alerts
|

Functional outcome in patients with thoracolumbar burst fractures treated with dorsal instrumentation and transpedicular cancellous bone grafting

Abstract: The aim of the study was to develop an insight into the impairments in spinal fracture patients, operatively treated with an internal fixator, and also into their ability to participate in daily living, return to work and quality of life as defined by the World Health Organization. Nineteen patients operated for a type A fracture of the thoracolumbar spine (T9-L4) between 1993 and 1998 in the University Hospital Groningen, the Netherlands, aged between 18 and 60 years, without neurological deficit were include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
22
0
5

Year Published

2004
2004
2009
2009

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 38 publications
5
22
0
5
Order By: Relevance
“…kyphotic deformation) does not seem to influence QoL after injuries of the thoracolumbar spine and, therefore, not omitted this parameter in our current study [9,10]. These findings are in line with the data published by other investigators [39,41,49].…”
Section: Quality Of Life Assessmentsupporting
confidence: 89%
See 1 more Smart Citation
“…kyphotic deformation) does not seem to influence QoL after injuries of the thoracolumbar spine and, therefore, not omitted this parameter in our current study [9,10]. These findings are in line with the data published by other investigators [39,41,49].…”
Section: Quality Of Life Assessmentsupporting
confidence: 89%
“…In line with this observation several other study groups have previously described quite similar results with regard to the SF-36 [7,39,41,49,62].…”
Section: Quality Of Life Assessmentsupporting
confidence: 88%
“…Additional transpedicular bone-grafting did not prevent from re-kyphosing and the reported loss of correction after posterior fixation was significant [2,46,49,50,100]. However, with regard to clinical outcome several authors reported good results with posterior stabilisation alone [65,75,84,100]. Therefore, the relevance of achieving an optimal ''technical/radiological result'' with anatomic alignment and definite stability by interbody fusion is still under debate.…”
Section: Discussionmentioning
confidence: 99%
“…Uþpakalinës, transpedikulinës stuburo fiksacijos metodo populiarumas iðlieka, nors esama praneðimø apie daþnas metalo konstrukcijø nuovargio lûþiø komplikacijas [20][21][22][23] bei didesnius korekcijos praradimus, palyginti su priekinës fiksacijos metodu [6,24]. Paaiðkinimas toks: daugelis ðio metodo ðalininkø teigia, jog trauminës deformacijos progresavimas, palyginti su pradine deformacija, yra nedidelis ir neturi átakos pacientø skundams [5,25,26], o metalo konstrukcijø lûþiø komplikacijø skaièiø galima sumaþinti ðalinant jas po 10-12 mën. Ðie argumentai nëra átikinami, todël pasirodo vis daugiau straipsniø, rekomenduojanèiø uþpakalinës fiksacijos metodà taikyti kartu su priekinës stuburo kolonos rekonstrukcija ir spondilodeze, ypaè tais atvejais, kai lûþusio slankstelio kûno suspaudimo laipsnis yra labai didelis [23, 24,27,28].…”
Section: Discussionunclassified
“…Mûsø tyrimo pagal NASS klausimynà rezultatai geresni uþ lëtiniais nugaros skausmais besiskundþianèiø ligoniø duomenis, bet nesiekia JAV gyventojø norminiø rodikliø. Roland-Morriso klausimyno vidurkis 5,9 atitinka literatûroje skelbiamus rezultatus, kurie svyruoja nuo 4,5 iki 8,4 [25,41,42]. Dël kultûriniø ir kalbiniø skirtumø tiesioginiø iðvadø ið ðiø palyginimø daryti negalime, taèiau galime teigti, kad metus po stuburo traumos 25,0% pacientø vargina nuolatiniai nugaros skausmai, ribojantys kasdienae veiklà.…”
Section: Diskusijaunclassified